MANAGEMENT OF SUSTAINABLE DEVELOPMENT OF THE ENTERPRISE FROM THE POSITION OF ENSURING ECONOMIC SECURITY (Development Service Industry Management, 2023)
The article examines the issue of managing the sustainable development of the enterprise from the standpoint of ensuring its economic security. An analysis of the main components of sustainable development: economic, social, environmental. The main directions of the enterprise's development in the aspect of harmonizing its economic goals of activity with social and environmental goals have been determined. It was determined that the achievement of the main goal of the enterprise - increasing profitability requires taking into account the requirements and needs of the social sphere and the need to support the ecological system - that is, preserving the environment and improving the quality of life. The article examines the theoretical aspects of sustainable development of the enterprise and economic security of the enterprise. The signs of sustainable development of the enterprise are determined. An analysis of scientists' interpretations of the sustainable development of the enterprise was carried out. It was determined that the concept of sustainable development is based on the main principles: ensuring the balance of the economy and ecology, ensuring the balance of the economic and social spheres, the implementation of tasks related to development, not only in the interests of today's generations, but also future ones, which have equal rights to resources . It has been studied that the sustainable development of the enterprise presupposes its ability to function and develop under the influence of factors of an unstable external environment. The need to build a mechanism for managing the sustainable development of the enterprise, taking into account its current and projected level of economic security, is argued. The article describes the main stages of the mechanism of managing the sustainable development of the enterprise.
Keywords: sustainable development; economic security; enterprise; concept; management